Guide to in‐field assessment of the painful equine eye. Issue 9 (4th November 2022) - de Oliveira, Chez; Dixon, Sam
Abstract : Background : Using simple equipment and a systematic approach, it is possible to perform a thorough ocular equine examination in the field. Good‐quality images and videos can be obtained on most smartphones and can prove invaluable both for monitoring the progress of ocular disease, or when seeking referral or advice from an ophthalmologist. Even in cases where referral is not an option, a significant amount can be achieved in the field by the first‐opinion practitioner. Aim of the article : This article sets out a logical and systematic approach to the ocular examination, and outlines how to interpret the examination findings in order to arrive at an accurate diagnosis and instigate an initial treatment plan.